Small business management and entrepreneurship - Stokes, David; Wilson, Nicholas (Thomson, 2006)
This text explores the contexts, choices and strategies facing the small business venture, including coverage of planning a new venture. It contains pedagogical features that include case material to explore the same case situation from a number of different but interrelated angles and chapter-end real world case studies.